Model Integrasi SJPH-CPPOB untuk UMK: Studi Kasus Produsen Yoghurt di Bogor: Integration Model SJPH–CPPOB for Micro and Small Enterprises (MSEs): a Case Study of a Yogurt Manufacturer in Bogor - Aji Jumiono; Aang Ahyarudin; Mir’atu Saa’diah Septiani; Mardiah Mardiah (Jurnal Ilmiah Pangan Halal, 2026)
This study aims to analyze the implementation and integration of the Halal Product Assurance System (Sistem Jaminan Produk Halal, SJPH) and Good Manufacturing Practices for Processed Foods (Cara Produksi Pangan Olahan yang Baik, CPPOB) among micro and small enterprises (MSEs), using PT XMJ—a yogurt producer in Bogor City—as a case study. The evaluation was conducted using five SJPH criteria stipulated in Kepkaban No. 20 of 2023 and the technical CPPOB standards issued by the Indonesian National Agency of Drug and Food Control (BPOM). The findings indicate that the adoption of both systems remains partial and has not been systematically documented. Convergence between SJPH and CPPOB is evident in sanitation, personnel hygiene, process control, and documentation. An integration model was therefore developed using an input–process–output framework, adjusted to the operational capacity of MSEs. The model is expected to streamline the implementation of both systems while ensuring halal compliance and product safety. Integrating SJPH and CPPOB offers opportunities for operational efficiency, improved product quality, and enhanced readiness for halal certification and processed food licensing. This study recommends strengthening management commitment, enhancing human resource training, and developing integrated procedures and documentation as strategic steps toward implementing a halal- and safety-assured quality system in the MSE sector.